Potential and Challenges of the Red and White Cooperative in Community Economic Empowerment in Makbalim Village, Sorong Regency - Isti Nur Laili Sanggel; Bambang Sunatar; Suharmoko Suharmoko (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the potential and challenges of the Merah Putih Cooperative in empowering the community economy in Makbalim Village, Sorong Regency. The Merah Putih Cooperative is a national program designed as an instrument for strengthening the community-based economy through the distribution of strategic commodities, supporting productive businesses, and strengthening economic access for rural and sub-district communities. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants include cooperative administrators, members, the community, and sub-district government officials. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, with data validity maintained through triangulation of sources, techniques, and time. The results show that the Merah Putih Makbalim Cooperative has great potential in economic empowerment, supported by local natural resources, community social capital, and support from the sub-district government. The distribution program for fertilizer, affordable basic necessities, and food logistics support are strategic steps to strengthen the community economy. However, the cooperative faces challenges such as limited human resource capacity, weak management and administration, low community understanding of cooperatives, and slow external assistance. The study concluded that this cooperative is in the early stages of institutional strengthening with promising economic potential, but requires increased institutional capacity, ongoing mentoring, and strengthening community participation so that it can function optimally as a driver of local economic empowerment.